Spatial modelling of groundwater potential in Zimbabwe using geographical information systems techniques. (24th November 2014) - Chikodzi, David; Mutowo, Godfrey
The research was aimed at modelling variations in groundwater potential within Zimbabwe. Input parameters used in the study were: lithology, groundwater productivity, slope, and depth to groundwater, faults, groundwater storage and their interrelationship. Each parameter was first individually classified according to how it promotes or constrains groundwater occurrence. The input parameters were then individually weighted to determine their importance to groundwater occurrence using analytical hierarchal processing (AHP). A geographical information system (GIS) was then used to combine the input parameters according to their assigned weights. Results showed that the areas of high groundwater potential cover 21.41%, moderate potential cover 35.10% and those of low potential cover 44.48% of the country. We conclude that, using known groundwater determinants as input parameters, we can use a geographical information system to map the spatial variations in groundwater potential.